VIRTUAL REALITY TECHNOLOGY APPLICATION FOR CONSERVATION ARCHITECTURE BUILDING - Bahar, Yudi Nugraha (Universitas Gunadarma, 2014)
Development of visualization and simulation technology through the Virtual-Reality (VR) is now very advanced in terms of quality of output (graphics, sound, touch), the ease, efficiency and user psychology equipment. Problems tend to arise in the development of advanced systems as early innovation in particular to the disciplines of architecture. This paper discusses the use of VR in the field of architecture, especially with regard to the preservation of historical heritage or digital preservation and conservation. So far many of the reconstruction of buildings and historical district tend to be made in 2D or video display and it is considered to be quite informative in terms of the generated virtual environment. But it is limited in terms of interaction and visualization with details and full-scale immersive quality that can only be provided by VR technology. VR allows heritage sites reconstructed with highly accurate, 3D models, interactive and real-time can be presented. Finally look so real that will facilitate feedback from anyone in particular building stakeholders. Keywords : Architecture, Conservation, Virtual-Reality